Navigating Ethical and Social Issues in Marketing Intelligence - Bagdi, Pooja (Journal of Advanced Research in Strategic Marketing Intelligence and Customer Engagement Optimization, 2025)
The growing use of marketing intelligence (MI) has transformed the way businesses understand and engage with customers, driving strategic decisions and innovation. However, as the reliance on MI increases, so do concerns about its ethical and social implications. This review explores the key ethical challenges businesses face, particularly in relation to privacy, data security, informed consent, and algorithmic fairness. It also highlights the social consequences of MI, such as potential biases, manipulation, and the impact on consumer trust. The paper emphasizes the need for organizations to strike a balance between leveraging data for competitive advantage and adhering to ethical principles, ensuring that marketing efforts do not compromise individual rights or societal well-being. Furthermore, it provides practical recommendations for businesses to mitigate risks associated with the use of MI, such as implementing transparent data practices, conducting algorithmic audits, and promoting consumer empowerment. Ultimately, the review aims to foster an approach to marketing intelligence that is both responsible and innovative, allowing businesses to thrive while maintaining public trust and contributing to the greater social good.